2016
DOI: 10.1111/jdv.13933
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of suitable starting doses of narrowband UVB in Asian vitiligo patients: a pilot study

Abstract: Results from phototest and tolerability of patients to doses higher than 280 mJ/cm may indicate that higher starting doses might be appropriate for Asian vitiligo patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Related studies on these diseases all suggested that the anti-inflammation effect of ADSCs occurs via the IL-1β pathway. Previous studies have shown that ADSCs affect the treatment of scars induced by P. acnes [ 44 ] and diabetic wound healing [ 45 47 ]. ADSCs have the advantage of being abundant, easy to obtain, and usable without ethical constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies on these diseases all suggested that the anti-inflammation effect of ADSCs occurs via the IL-1β pathway. Previous studies have shown that ADSCs affect the treatment of scars induced by P. acnes [ 44 ] and diabetic wound healing [ 45 47 ]. ADSCs have the advantage of being abundant, easy to obtain, and usable without ethical constraints.…”
Section: Discussionmentioning
confidence: 99%